Multistage concentrated sea water fuel extraction system - Lin Xishi (2016)
The utility model provides a multistage concentrated sea water fuel extraction system for draw including deuterium ionic liquid fuel from the sea water, it includes: the elementary sea water extraction element and the multistage sea water fine filtration device that concatenate each other, be equipped with the filter among elementary sea water extraction element and the multistage sea water fine filtration device respectively, run through elementary sea water extraction element and multistage sea water fine filtration device in proper order with the sea water through the pipeline, filter the fresh water and the impurity of the aquatic of going to sea respectively through multistage reverse osmosis membrane device, isolate and contain deuterium ionic sea water concentrate as liquid fuel. 本实用新型提供了种多级浓缩海水燃料提取系统，用于从海水中提取含氘离子的液体燃料，其包括：相互串接的初级海水提取装置和多级海水精滤装置，所述初级海水提取装置和多级海水精滤装置中分别设有过滤器，通过管路将海水依次贯穿初级海水提取装置和多级海水精滤装置，分别经过多级反渗透膜装置过滤出海水中的淡水和杂质，分离出含有氘离子的海水浓缩液作为液体燃料。